Descriptive study: anemia and concentration levels in elementary school students receiving free nutritional meals - Dely Ria Simanjuntak; Dely Maria (International Journal Of Community Medicine And Public Health, 2026)
Background: Elementary school is a crucial period in a child's growth and development, both physically, cognitively, and psychosocially. During this phase, children are developing basic learning skills, which are greatly influenced by their health and nutritional status. Breakfast plays a strategic role in meeting a child’s daily energy and nutrient needs. Morning food intake contributes to stable blood glucose levels, which the brain needs for cognitive functions such as attention and concentration. In addition to breakfast habits, anemia is still common among school-age children. Anemia, particularly iron deficiency anemia, can disrupt oxygen transport to body tissues, including the brain, potentially reducing children’s concentration, physical endurance, and learning ability. Methods: This was a descriptive study, with 82 students receiving MBG as respondents. Data collection was carried out 03 April 2025-03 September 2025. Active 5th grade elementary school students and who were able to read, willing to participate as research subjects and sign the informed consent were included. Statistics using descriptive methods. Statistical tests described the nutritional status, anemia, and concentration levels of the students. Results: Students received MBG for three months. 35.4% were anemic and 64.6% were non-anemic. Meanwhile, concentration levels were categorized as poor (50%), and very good (2.4%). Conclusions: The results of this study are expected to provide basic information for schools, health workers, and parents in designing promotive and preventive efforts to support children’s health and learning abilities from an early age.